Policing the Poachers in a Western State: Game Wardens and the Use of Discretion - Eliason, Stephen L. (International Journal of Rural Criminology, 2021)
Game wardens are specialized law enforcement officers responsible for enforcing hunting and fishing laws designed to protect wildlife resources. While performing their duties they encounter a variety of wrongdoers that range from first time offenders to those who are chronic violators of the law. Little research exists on the use of discretion by wildlife law enforcement officers, or their attitudes toward offenders. This study took a qualitative approach to data collection and examined the use of discretion by game wardens in Montana and their perceptions of habitual poachers. Factors that were associated with the use of discretion included intent of the violator, seriousness of the offense, and age of the violator. The majority of wardens in the study expressed negative opinions toward violators that were chronic offenders. Findings contribute to our understanding of law enforcement attitudes and decision making.